The Prediction of Repeated Violence Among Individuals With Serious Mental Disorders: Situational Versus Dispositional Factors - Harris, Michelle N. (Journal of interpersonal violence, 2021)
The question we attempt to answer in this study is why some individuals with serious mental illness engage in repeated violence, while others do not. There appear to be two perspectives that may explain repeated violence: one that emphasizes situational factors and one that emphasizes dispositional factors. Situational factors are those that are constantly changing within one’s life, whereas dispositional factors are those that remain relatively stable over time. Therefore, dispositional factors would theoretically put individuals with serious mental illness at stable risk for repeated violence because these factors remain relatively stable over time. In fact, perhaps individuals with mental illness repeatedly engage in violence because they have a dispositional trait (like impulsivity, for example) that puts them at stable risk for repeated violence. Conversely, situational factors would theoretically explain why individuals do not engage in repeated violence because they are transient and constantly changing. Therefore, perhaps one desists from violence because some situational factors changed in that individual’s life. Using data from the MacArthur Violence Risk Assessment Study (i.e., MacRisk), a longitudinal study of people with serious mental illness, repeated violence was evaluated across waves. A multilevel logistic regression model was employed. Results indicate that both situational and dispositional factors are significantly associated with repeated violence. Specifically, situational factors such as marital status, drug use, perceived stress, and time away from the psychiatric hospital and dispositional factors such as personality traits including agreeableness, conscientiousness, openness, and extraversion are all significantly associated with repeated violence. These findings have important policy implications regarding criminal justice intervention and clinical practice.